Endoscopic Phenotype of Monoallelic Carriers of MUTYH Gene Mutations in the Family of Polyposis Patients: A Prospective Study. Issue 4 (April 2019) - El Hachem, Noha; Abadie, Caroline; Longy, Michel; Colas, Chrystelle; Fert-Ferrer, Sandra; Leroux, Dominique; Grandval, Philippe; Prieur, Fabienne; Collonge-Rame, MarieAgnes; Faivre, Laurence; Fricker, Jean-Pierre; Zerbib, Frank; et al.
Abstract : BACKGROUND: Almost no prospective data on endoscopy in MUTYH monoallelic carriers are available. OBJECTIVE: This study aimed to define the prevalence of colorectal and duodenal adenomas in a population of people presenting with a single mutation of the MUTYH gene and being first-degree relatives of biallelic MUTYH mutation carriers. DESIGN: This study is a prospective cohort evaluation. PATIENTS: Patients were first-degree relatives of a patient who had polyposis with biallelic MUTYH mutation and carrying a single gene mutation of the gene from 12 French centers. SETTINGS: This is a multicenter study. INTERVENTION: Detailed data on life habits (tobacco, alcohol, and nonsteroidal anti-inflammatory drugs), extraintestinal manifestations, and germline analysis were recorded. Complete endoscopic evaluation (colonoscopy and upper endoscopy) with chromoendoscopy was performed. RESULTS: Sixty-two patients were prospectively included (34 women (55%), mean age of 54, range 30–70 years). Thirty-two patients (52%) presented with colorectal polyps at colonoscopy. Of these patients with polyps, 15 (25%) had only adenomas, 8 (13%) had only hyperplastic polyps, 1 (1%) had sessile serrated adenomas, and 8 (13%) had adenomas and/or sessile serrated adenomas. We detected, in total, 29 adenomas with low-grade dysplasia, 5 adenomas with high-grade dysplasia, and 6 sessile serrated adenomas. Fourteen patients (23%) presented with a single adenoma, and 10 (16%) had 1 to 5 adenomas. No patient had more than 5 adenomas. At upper endoscopy, 3 had a limited number of fundic gland polyps; none had duodenal adenomas. The 2 main missense mutations c.1145G>A, p.Gly382Asp and c.494A>G, p.Tyr165Cys were associated with the development of colorectal adenomas/serrated polyps in these monoallelic carriers. LIMITATIONS: This study was limited by the small number of patients. CONCLUSIONS: This prospective study provides unique prospective data suggesting that monoallelic mutation carriers related to patients with polyposis show no colorectal polyposis and have very limited upper GI manifestations justifying an endoscopic follow-up. See Video Abstract at http://links.lww.com/DCR/A862 .